2022
DOI: 10.3389/fonc.2022.1012646
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of further axillary dissection for sentinel lymph node micrometastases in female breast cancer: A competing risk analysis using the SEER database

Abstract: BackgroundSentinel lymph node (SLN) biopsy has been widely recognized as an excellent surgical and staging procedure for early-stage breast cancer, and its development has greatly improved the detection of micrometastases. However, the axillary treatment of micrometastasis has been the subject of much debate.MethodsWe identified 427,131 women diagnosed with breast cancer from 2010 to 2018 in the Surveillance, Epidemiology, and End Results (SEER) database. Patients whose nodal status was micrometastases (pTxN1m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The NOS was used to assess the quality of evidence in non-RCT trials. Five studies received a rating of seven or more stars, indicating high quality ( 15 , 16 , 19 , 21 , 35 ).Seven studies received a rating of six stars ( 11 , 20 , 22 , 23 , 26 , 34 , 36 ), and six studies were assessed as having four to five stars (See Table 1 ). The GRADEpro GDT tool was used to classify the evidence of RCTs comparing ALND to SLNB alone for patients with clinical node-negative early-stage breast cancer and positive sentinel lymph nodes.…”
Section: Resultsmentioning
confidence: 99%
“…The NOS was used to assess the quality of evidence in non-RCT trials. Five studies received a rating of seven or more stars, indicating high quality ( 15 , 16 , 19 , 21 , 35 ).Seven studies received a rating of six stars ( 11 , 20 , 22 , 23 , 26 , 34 , 36 ), and six studies were assessed as having four to five stars (See Table 1 ). The GRADEpro GDT tool was used to classify the evidence of RCTs comparing ALND to SLNB alone for patients with clinical node-negative early-stage breast cancer and positive sentinel lymph nodes.…”
Section: Resultsmentioning
confidence: 99%
“…Then, 72 papers were retrieved for full-text review. Finally, 30 reports for 26 studies were included in the systematic research and meta-analysis according to the inclusion and exclusion criteria [ 12 , 13 , 30 57 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen papers compared the OS between patients treated with ALND and SLNB only [ 13 , 31 , 34 , 37 , 39 , 40 , 42 , 44 , 48 , 50 , 51 , 53 , 55 , 57 ]. A fixed-effect statistical model (Q-test: p = 0.26 and I 2 = 16%) revealed that the OS was not significantly different between the SLNB only and ALND groups (HR = 0.97, 95% CI: 0.92–1.03, p = 0.37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, the sub‐hazard ratio (SHR) was determined to be similar to the hazard ratio, but taking into consideration the hazard of competing events, which was suitable for exploring CVD‐related mortality among cancer patients. 16 , 17 In our study, competing risk regression was used to evaluate the association between age at diagnosis and CVD‐related mortality among major gastrointestinal cancers. Patients who died from cancer were regarded as competing events.…”
Section: Methodsmentioning
confidence: 99%